2009
DOI: 10.1007/s00467-009-1254-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of catheter-related bacteremia in children on hemodialysis: time for action

Abstract: This editorial commentary discusses the strategies for prevention of catheter-related bacteremia (CRB) in children on hemodialysis, which is associated with high morbidity and the increase of hospital cost. There is evidence that the use of arteriovenous fistulae in children on hemodialysis is associated with lower infection rates. Therefore, the use of catheters in these patients should be decreased by improving arteriovenous fistulae use rates or by increasing peritoneal dialysis patient recruitment. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…Yet, vascular catheter use among children on chronic HD is high . Actually, CVCs are often the only form of vascular access in young children with relatively small vessels, as the construction of an AVF might be technically very difficult or even impossible .…”
mentioning
confidence: 99%
“…Yet, vascular catheter use among children on chronic HD is high . Actually, CVCs are often the only form of vascular access in young children with relatively small vessels, as the construction of an AVF might be technically very difficult or even impossible .…”
mentioning
confidence: 99%
“…12,13,16,26 The Center for Disease Control recommends the use of 2% chlorhexidine, 25 but this recommendation is based on studies involving mainly adult intensive care patients with temporary catheters, and very few data are available concerning patients with tunneled HD catheters. 12,13,16,26 The Center for Disease Control recommends the use of 2% chlorhexidine, 25 but this recommendation is based on studies involving mainly adult intensive care patients with temporary catheters, and very few data are available concerning patients with tunneled HD catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal exit-site care is essential in order to prevent catheter-associated infections in patients on chronic HD, and the choice of the exit-site cleaning agent is critical. 12,13,16,26 The Center for Disease Control recommends the use of 2% chlorhexidine, 25 but this recommendation is based on studies involving mainly adult intensive care patients with temporary catheters, and very few data are available concerning patients with tunneled HD catheters. [17][18][19][20][21][22][23][24] It is therefore not surprising that a recent European survey found that different CVC management protocols are used in pediatric dialysis units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the challenges inherent to managing children with sepsis, this approach and other related efforts (e.g. antimicrobial lock solutions) aimed at preventing sepsis events by eliminating common triggers are not trivial achievements [77, 78]. Indeed, the KDIGO group’s AKI guidelines devote a chapter on vascular access for RRT in AKI with special attention towards decreasing the rate of catheter-related infections [79].…”
Section: Sepsis Prevention Strategiesmentioning
confidence: 99%